Imagining the Black Female Body Reconciling Image in Print and Visual Culture - Henderson, C.; Henderson, C. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2010)
This volume explores issues of black female identity through the various "imaginings" of the black female body in print and visual culture.  Contributions emphasize the ways in which the black female body is framed and how black women (and their allies) have sought to write themselves back into social discourses on their terms.